2009
DOI: 10.1016/j.immuni.2008.12.018
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocytes Exit Lymph Nodes through Cortical Lymphatic Sinusoids by a Mechanism Independent of Sphingosine-1-Phosphate-Mediated Chemotaxis

Abstract: Sphingosine-1 Phosphate (S1P) helps mediate lymphocyte egress from lymph nodes, yet significant mechanistic questions remain. Here we show that B lymphocyte egress sites exist close to lymph node follicles. Recent B cell emigrants localize towards follicle centers, while longer-term residents tend towards cortical sinusoids. Exiting B lymphocytes squeeze through apparent portals in the lymphatic endothelium. Treatment with the S1P receptor agonist FTY720 empties the cortical sinusoids of lymphocytes, blocks ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
112
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(122 citation statements)
references
References 40 publications
9
112
1
Order By: Relevance
“…7F), indicating that S1P 1 receptor stimulation mostly accounts for FTY720-induced egress inhibition, and S1P 1 receptor downregulation is a secondary, less important event, at least in case of FTY720 treatment. This is in line with recent reports showing the requirement of FTY720 phosphorylation by SK2 for efficient lymphopenia at low FTY720 concentrations (30,31) and the independence of B cell exit from S1P-mediated chemotaxis (40). It also explains the observation that S1P 1 receptor agonists and not antagonists were able to induce lymphopenia in vivo, although antagonists could reverse lymphopenia induced by agonists (39).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…7F), indicating that S1P 1 receptor stimulation mostly accounts for FTY720-induced egress inhibition, and S1P 1 receptor downregulation is a secondary, less important event, at least in case of FTY720 treatment. This is in line with recent reports showing the requirement of FTY720 phosphorylation by SK2 for efficient lymphopenia at low FTY720 concentrations (30,31) and the independence of B cell exit from S1P-mediated chemotaxis (40). It also explains the observation that S1P 1 receptor agonists and not antagonists were able to induce lymphopenia in vivo, although antagonists could reverse lymphopenia induced by agonists (39).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand S1P 1 receptor agonists prevent lymphocytes from crossing the lymphatic endothelium, which was blocked by otherwise inactive S1P 1 receptor antagonists (14,39). Furthermore B cells seem to exit lymph nodes independently from S1P-mediated chemotaxis (40). The contribu- 6 HTC 4 cells were incubated for 15 h with indicated concentrations of AAL(R), AAL(S), FTY720, staurosporine, calphostin C, and GF109203X.…”
Section: Discussionmentioning
confidence: 99%
“…Most research on lymphocyte egress from DLNs has been carried out in homeostatic conditions and focused either on mechanisms that lymphocytes use to reach efferent lymphatic vessels, including regulation of CCR7 (7) and sphingosine 1-phosphate receptor-1 (S1P1) expression (18,29,30,53,54), or on mechanisms operating at the level of lymphatic endothelial barriers (31,55). We showed that the expansion of cortical and medullary sinuses in the late phase of inflammation functionally supports the egress of naive lymphocytes from LNs.…”
Section: Discussionmentioning
confidence: 91%
“…We hypothesized that the return of lymphocyte egress to baseline levels at day 14 postimmunization compared with day 4 may occur through an expansion of cortical and medullary sinuses, because they are the major exit paths for lymphocytes (29)(30)(31). To investigate this possible scenario, we developed a strategy to distinguish cortical and medullary sinuses from subcapsular sinuses given that specific markers to differentiate them are currently lacking.…”
Section: Preferential Expansion Of Cortical and Medullary Sinuses Occmentioning
confidence: 99%
“…Based on these observations, a multistep model was proposed delineating cortical sinus probing, S1P 1 -dependent entry, and flow-based capture of T cells as critical steps for their lymph node exit. B cell exit was also shown to occur through cortical lymphatic sinusoids, although by a mechanism that is likely independent of sphingosine 1-phosphate-mediated chemotaxis (9).…”
mentioning
confidence: 99%